Solar powered battery charger with state of charge indicator circuit - Janice Jothi, Pandian (2009)
Solar energy is one of the many forms of renewable energy on earth. This energy can be harnessed by using a solar cell or photovoltaic cell which converts sunlight directly into electricity. Solar power can also be used in many small electrical devices such as battery chargers. In this project, a solar powered battery charger with a state of charge indicator circuit is developed to charge AA batteries and to show indication to the user when the batteries reach a fully charged state. The primary benefit of using a solar powered battery charger is that it is one of the cheapest forms of recharging batteries. Apart from this, solar powered battery chargers are fast gaining popularity as they have been proven to be handy in many situations especially in the outdoors, being portable and user friendly. In this project, a constant current source is provided to the batteries in order to recharge it and the state of charge indicator circuit is developed with an adjustable precision Zener shunt regulator. Once the batteries are fully charged, an LED will light up to show the user that the batteries can now be used reused.